Pt–M Complexes (M=Ag, Au) as Models for Intermediates in Transmetalation Processes. Issue 52 (21st August 2018) - Baya, Miguel; Belío, Úrsula; Campillo, David; Fernández, Israel; Fuertes, Sara; Martín, Antonio
Abstract: Heteropolynuclear complexes [(CNC)(PPh3 )PtM(PPh3 )]ClO4 [M=Au (1 ), Ag (2 )] and [{Pt(CNC)(PPh3 )}2 M]ClO4 [M=Ag (3 ), Au (4 ); CNC=2, 6‐diphenylpyridinate] were prepared and studied by X‐ray crystallography, spectroscopic techniques, and DFT calculations. The X‐ray crystal structures of1, 3, and4 confirmed the existence of Pt−M bonds and M⋅⋅⋅ C ipso interactions involving one of the phenyl fragments of CNC. Their NMR spectra showed the persistence of the Pt−M interactions in solution and also revealed an intramolecular metronome‐like dynamic process consisting of back‐and‐forth motion of the acidic M fragments along the C‐Pt‐C axis. DFT calculations on these complexes identified two main orbital interactions between the [PtCNC] and [M] + fragments, namely, donation from the former to a vacant orbital of the latter and much weaker backdonation from the acidic M to the Pt fragment. Overall, the strength of the [Pt]⋅⋅⋅ M interactions is higher for the gold compounds than for their silver counterparts. The interaction between the acidic center (silver or gold) and the carbon atom of one of the phenylene rings in these heteropolymetallic complexes can be envisaged as the first step in a process of interchange of aryl ligands. However, the ligand exchange cannot progress further due to the polydentate nature of the CNC ligand, and therefore these structures can be considered as frozen snapshots of a transmetalation reaction that has been arrested at different stages of the process. Abstract : Like a metronome : Heterometallic complexes [(CNC)(PPh3 )PtM(PPh3 )]ClO4 and [{Pt(CNC)(PPh3 )}2 M]ClO4 (M=Ag, Au; CNC=2, 6‐diphenylpyridinate) show a dynamic behavior in solution that can be described as metronome‐like a back‐and‐forth motion of the acidic M fragments along the C‐Pt‐C axis (see figure). Nevertheless, their X‐ray structures show strong M−C interactions and can be considered as frozen snapshots of a transmetalation reaction that has been arrested at different stages of the process.